2022
DOI: 10.3390/ijerph19095767
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Characteristics of COVID-19 Cases in Non-Italian Nationals in Sicily: Identifying Vulnerable Groups in the Context of the COVID-19 Pandemic in Sicily, Italy

Abstract: As in other parts of the world, undocumented migrants in Italy suffer worse health status due to their immigration enforcement situation and other vulnerabilities such as precarious illegal jobs, exploitation and abuse or barriers to higher education, with higher prevalence of chronic noncommunicable diseases. The COVID-19 pandemic, as other pandemics, has not affected everyone equally. The undocumented was one of the most affected groups with regard to hospitalization rates and mortality worldwide. Sicily is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…We also reported slightly higher odds of being hospitalised for migrants. This is consistent with previously published research from other European countries ( 13 , 15 , 17 , 18 , 31 , 36 ). These differences in hospitalisation for migrant patients could be attributed to a delay in seeking healthcare attention by migrants.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also reported slightly higher odds of being hospitalised for migrants. This is consistent with previously published research from other European countries ( 13 , 15 , 17 , 18 , 31 , 36 ). These differences in hospitalisation for migrant patients could be attributed to a delay in seeking healthcare attention by migrants.…”
Section: Discussionsupporting
confidence: 94%
“…European studies have described heterogeneous results; while some found no significant differences in health outcomes due to SARS-CoV-2 infection between native and immigrant population, others reported higher risk of infection and hospitalisation rates (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). There have been a few studies from Spain, but most were performed at the beginning of the pandemic and had also conflicting results; some concluded there were no significant differences in ICU admission or mortality, while others stated that some groups of immigrants had higher risk of ICU admission (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Johnson-Agbakwu et al showed the inequities in mortality between white and Black populations [33] and how these have been exacerbated by the recent COVID-19 pandemic, seeking to propose measures to resolve this situation. Also in Italy, a study on the epidemiological characteristics of COVID-19 cases in non-Italian nationals confirmed that compared with Italians, undocumented foreigners have a greater risk of severe clinical outcomes [34]. Along the same lines, Ponce-Blandón et al analyzed the complex reality faced by migrants who cross the Strait of Gibraltar for a better life [35], identifying various cultural barriers encountered by health professionals who were unable to provide culturally appropriate help when they were caring for people of different races/ethnicities: factors such as language, religious beliefs, cultural habits and prejudices, among others [36].…”
Section: Discussionmentioning
confidence: 91%
“…Clinical manifestations of COVID-19 include fever, cough, and dyspnea ( 4 , 5 ). However, loss of smell and taste, and in some cases, diarrhea have also been reported ( 6 ). The number of affected people is growing.…”
Section: In Briefmentioning
confidence: 99%